Tingkat Efektifitas Dan Efisiensi Terhadap Kebutuhan Pelanggan Pengguna Jasa Light Rail Transit - Sonya Sidjabat; Tri Mulyani Setyowati; Erni Pratiwi Perwitasari (Institut Transportasi dan Logistik Trisakti, 2021)
The purpose of this study is to determine and analyze the level of effectiveness and efficiency of LRT services using path analysis. Calculations and data processing were carried out using SPSS ver 26 with primary data types taken from respondents using the LRT route. Data collection was done by distributing a list questions via google form to 105 respondents. This study uses the Ordinary Least Square regression model which produces research findings that customer needs are not able to mediate the effect of the level of effectiveness and efficiency on the demand for LRT services, or it can be said that the level of effectiveness and efficiency has a direct positive and significant effect on the demand for services. LRT without going through customer requirements. This can be due to the fact that LRT Transportation users because there are still many other transportation options that have advantages over LRT, such as punctuality and the use of more practical transportation.